EFFICACY OF BRIVARACETAM IN PEDIATRIC EPILEPSY: AN UP-TO-DATE - Antonio Nicotera (Associazione Italiana Giovani Medici, 2021)
Among the newest antiepileptic drugs, brivaracetam (BRV), previously known as “ucb34714”, is one of the most interesting molecules available, increasingly getting the attention of researchers. The clinical efficacy of BRV as adjunctive therapy has been extensively assessed in six randomized, controlled, phase III trials, the results of which demonstrated BRV efficacy in reducing seizures at the dosage of 20–200 mg/day. However, to date, only few data on the pediatric population are available. Here we briefly report the data available on BRV and its usage in the pediatric population suffering from epilepsy to highlight the potential benefits of this drug in this population.